Prototyping and Usability Evaluation of Road Safety Education Courseware for Primary Schools in Malaysia - Zulkifli, Abdul Nasir; Faisal Mohamed, Nur Fadziana; Qasim, Mustafa Moosa; Abu Bakar, Nur Afiqah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The increasing number of road accidents and deaths among children in Malaysia is a concern. One of the main causes stems from lack of knowledge and skills in dealing with the complexity and condition of the road system. Recognizing the significance of road safety among students, road safety education has been introduced to primary schoolsby the Ministry of Education in 2008. Initially it was blended into the Malay language subject with the goal to equip the children withthe knowledge and skills about road safety.However, road safety teaching and learning still uses the conventional methods without the use of specialized tools. This paper introduces ROSE courseware, a specialized learning tool developed to meet the needs of the Malaysian primary school curriculum for road safety education. Its learning environment is a blend of virtual reality, augmented reality and interactive multimedia, which enables children to understand and acquire skills related to road safety through interactive, real-time and immersive learning tool. In order to receive the children’s feedbacks pertaining to their experience in interacting with the ROSE courseware, a usability evaluation was conducted. The results show that the children strongly agreed on the usefulness, information quality and interface quality of the ROSE courseware.